Comparative Epidemiology of Streptococcus pyogenes emm-Types Causing Invasive and Noninvasive Infections in French Children by Use of High-Resolution Melting-Polymerase Chain Reaction. Issue 6 (June 2015) - d'Humières, Camille; Bidet, Philippe; Levy, Corinne; Béchet, Stéphane; Bonacorsi, Stéphane; Bingen, Edouard; Cohen, Robert
<x xml:space="preserve">Abstract</x> Background: This study aims to analyze the epidemiology of Group A streptococci (GAS) emm-types causing invasive and noninvasive infections in French children. Methods: From September 2009 to May 2011, we analyzed GAS isolates from 585 pharyngitis, 125 invasive infections and, for the first time in France, 32 healthy carriers. M protein gene (emm) typing of the isolates was carried out by a new rapid technique, combining 3 multiplex-polymerase chain reactions (PCRs) coupled to high-resolution melting (HRM) curves, able to detect 13 major emm-types (emm 1, 3, 4, 6, 11, 12, 22, 28, 75, 77, 87, 89 and 102). Results: GAS belonging to emm-type 1 were more frequently found among invasive infections than among pharyngitis (24.0% vs. 11.5%, P < 0.001); emm 4 and 89 were more common in pharyngitis than in invasive infections (emm-type 4, 17.4% vs. 6.4%, P = 0.002 and emm-type 89, 9.9% vs. 2.4%, P = 0.006, respectively) and emm 3 and 4 were more common in cases of pharyngitis associated with scarlet fever (21.6% vs. 6.0%, P < 0.001 and 29.3% vs. 14.5%, P < 0.001, respectively). Conclusion: HRM method enables the rapid emm-typing of a large number of isolates in epidemiological studies. Comparison of GAS causing invasive and noninvasive infections in the same population of children displays an unbalanced repartition of emm-types.